2022
DOI: 10.3390/md20100601
|View full text |Cite
|
Sign up to set email alerts
|

Revalorization of Microalgae Biomass for Synergistic Interaction and Sustainable Applications: Bioplastic Generation

Abstract: Microalgae and cyanobacteria are photosynthetic microorganisms’ sources of renewable biomass that can be used for bioplastic production. These microorganisms have high growth rates, and contrary to other feedstocks, such as land crops, they do not require arable land. In addition, they can be used as feedstock for bioplastic production while not competing with food sources (e.g., corn, wheat, and soy protein). In this study, we review the macromolecules from microalgae and cyanobacteria that can serve for the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 160 publications
(169 reference statements)
0
3
0
Order By: Relevance
“…For instance, Mathiot et al [122] reported synthesis of substantial amounts (49% w/w) of starch bioplastics under sulfur-scarce conditions by Chalamydomonas reinhardtii 11-32A after 20 d. In addition, Chlorella sorokiniana produced 38% w/w starch during cultivation at high light intensity and a low nitrogen concentration of 300 µmolm −2 s −1 and 32 mg/L, respectively [121]. The productivity of this polymer is dependent on strain type and growth conditions, and differs significantly among microalgae [123,124]. Remarkably, in one study, Chlorella sp.…”
Section: Starch-based Biopolymersmentioning
confidence: 99%
“…For instance, Mathiot et al [122] reported synthesis of substantial amounts (49% w/w) of starch bioplastics under sulfur-scarce conditions by Chalamydomonas reinhardtii 11-32A after 20 d. In addition, Chlorella sorokiniana produced 38% w/w starch during cultivation at high light intensity and a low nitrogen concentration of 300 µmolm −2 s −1 and 32 mg/L, respectively [121]. The productivity of this polymer is dependent on strain type and growth conditions, and differs significantly among microalgae [123,124]. Remarkably, in one study, Chlorella sp.…”
Section: Starch-based Biopolymersmentioning
confidence: 99%
“…More importantly, microalgae can effectively suppress the growth of bacterial strains through the interaction with their excretion products, such as fatty acids. [ 277 ]. Hence, C. reinhardtii and H. pluvialis have expressed additional antimicrobial and antifungal proteins (ToAMP4 or antimicrobial peptide piscidin-4 gene).…”
Section: Current Issues and Future Prospectsmentioning
confidence: 99%
“…Within microorganisms, microalgae distinguish themselves not only for their bioplastic production potential [ 17 ] but also for water treatment applications [ 18 ] and the production of biofertilizers, biofuels, food supplements, pharmaceutical products, and nutraceuticals, among others. Interestingly, microalgae can synthesize biopolymers, such as polyhydroxybutyrate (PHB) and polyhydroxyalkanoates (PHA) through photosynthetic processes during their cultivation [ 16 , 19 ]. The relevance of PHB and PHA is based on their likeness to propylene, a highly used oil-based plastic, and in the fact that both biopolymers present a high natural degradation rate in the environment [ 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%